Comprehensive design of uniform robust exact disturbance observer and fixed‐time controller for reusable launch vehicles. Issue 5 (9th January 2018) - You, Ming; Zong, Qun; Tian, Bailing; Zhao, Xinyi; Zeng, Fanlin
Abstract : The comprehensive design of uniform robust exact disturbance observer (UREDO) and fixed‐time controller for reusable launch vehicles is investigated. A UREDO which can estimate the disturbance after a fixed‐time independent of the initial error is presented. Based on the disturbance estimation, a non‐singular terminal sliding mode controller is designed to ensure that the guidance command can be tracked within a fixed‐time in the presence of model uncertainties and external disturbances. A proof of the fixed‐time convergence of the closed‐loop system under the control scheme is derived with complete stability analysis using the Lyapunov technique. The features of the proposed control scheme contain that the disturbance estimation, as well as the attitude tracking, can be achieved within a fixed‐time, which is independent of initial conditions and the derivative information of states is not essential, which is valuable in engineering application. Numerical simulations are performed to demonstrate the fixed‐time convergence performance of the proposed control scheme.